2005
DOI: 10.1016/j.atmosenv.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of inorganic and carbonaceous materials in PM2.5 in Nanjing, China

Abstract: PM 2.5 samples were collected at an urban and a suburban site in Nanjing, China in 2001. They were analyzed for inorganic ions, elemental carbon, organic carbon (OC), water-soluble organic carbon (WSOC), and individual WSOC and nonpolar organic species. Sulfate and organic matter were the two most abundant constituents in these samples. Sulfate accounted for an average of 23% (urban site) and 30% (suburban site) of the identified aerosol mass.Organic matter accounted for an average of 37% (urban) and 28% (subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
120
6
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 261 publications
(145 citation statements)
references
References 56 publications
16
120
6
3
Order By: Relevance
“…Almost everywhere, do we find a mixture of roughly comparable amounts of organic matter, soluble inorganic species (ammonium, nitrate and sulphate) and insoluble components (mineral dust and soot carbon; Malm et al 1994;Shrestha et al 1997;Zappoli et al 1999;Andreae et al 2002;Putaud et al 2004;Sun et al 2004;Yang et al 2005). The fairly constant proportion of soot carbon-a tracer of combustion and pollution in general-in spite of great variations in absolute aerosol concentrations, suggests that most of the Northern Hemisphere atmosphere is nowadays filled with pollution aerosols, at variable degrees of dilution.…”
Section: Aerosols: Past Present and Futurementioning
confidence: 99%
“…Almost everywhere, do we find a mixture of roughly comparable amounts of organic matter, soluble inorganic species (ammonium, nitrate and sulphate) and insoluble components (mineral dust and soot carbon; Malm et al 1994;Shrestha et al 1997;Zappoli et al 1999;Andreae et al 2002;Putaud et al 2004;Sun et al 2004;Yang et al 2005). The fairly constant proportion of soot carbon-a tracer of combustion and pollution in general-in spite of great variations in absolute aerosol concentrations, suggests that most of the Northern Hemisphere atmosphere is nowadays filled with pollution aerosols, at variable degrees of dilution.…”
Section: Aerosols: Past Present and Futurementioning
confidence: 99%
“…Recently, fine particles (PM 2.5 ) have received much more attention than coarse particle (PM 10 ) (Yang et al, 2005;Feng et al, 2007;Li et al, 2008;Li et al, 2009), as fine particles can travel more deeply into the human lungs, reaching the alveolar region of the respiratory system. They also take along higher contributions of toxic species harming health, higher contributions of light absorption species and light scattering species that affect visibility and the climate more than coarse particles (Kok et al, 2006;Polichetti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also it is observed that the presence of Cl − suggests that this may come from combustion emissions during cooking, coal cars, vegetation burning and incineration [25] [16] The presence of K + in the aqueous extracts from PM2.5 may well have a geological origin, or to be related to emissions from biomass burning [26]. It is likely that for the city of Cuernavaca part of the K + could be originated from soil particles, due to the significant correlation with Ca 2+ [26].…”
Section: Nomentioning
confidence: 99%